2014
DOI: 10.1007/s00044-014-0966-4
|View full text |Cite
|
Sign up to set email alerts
|

Elaborate ligand-based modeling reveals new human neutrophil elastase inhibitors

Abstract: Human neutrophil elastase inhibitors (HNE-Is) have been recently implicated in inflammatory diseases. Accordingly, we applied a drug discovery workflow to unveil novel inhibitory HNE leads via combining pharmacophore modeling, quantitative structure-activity relationship (QSAR) analysis, and in silico screening. We employed the pharmacophoric models and associated QSAR equation to screen the National Cancer Institute (NCI) list of compounds. Virtual screening identified 14 novel leads from NCI compounds. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Greene et al 13 built a pharmacophoric model based on the interactions of the crystallographic complex between HNE and methoxysuccinyl-Ala-Ala-Pro-alanine inhibitor, nevertheless no hit activities were reported for validation purpose. Habash et al 14 recently also reported a pharmacophoric model based on a known inhibitor training set leading to hit identication with discreet mM activities. In the present work we generate a ligand-based pharmacophoric model with MOE (Molecular Operating Environment) soware.…”
Section: Resultsmentioning
confidence: 99%
“…Greene et al 13 built a pharmacophoric model based on the interactions of the crystallographic complex between HNE and methoxysuccinyl-Ala-Ala-Pro-alanine inhibitor, nevertheless no hit activities were reported for validation purpose. Habash et al 14 recently also reported a pharmacophoric model based on a known inhibitor training set leading to hit identication with discreet mM activities. In the present work we generate a ligand-based pharmacophoric model with MOE (Molecular Operating Environment) soware.…”
Section: Resultsmentioning
confidence: 99%
“…Enaminones bearing a 3,4‐dihydroquinoxalin‐2(1 H )‐one core (QOs) are a promising class of biologically active compounds. They were found to exhibit anticancer, anti‐inflammatory, antidiabetic, analgesic, antiviral, and antimicrobial activities (Figure ). In addition, these compounds are versatile and available building blocks enabling synthesis of various quinoxaline‐based heterocyclic systems…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these compounds are versatile and available building blocks enabling synthesis of various quinoxaline-based heterocyclic systems. [7] General synthetic approaches to QOs involve interaction of acylpyruvic acids I, [1a,6a,b,7a] furan-2,3-diones II, [8] and acetylenedicarboxylates III [6d] with o-phenylenediamines, various condensations of quinoxalin-2(1H)-ones IV [2,9] (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mashevskaya et al reported about an antimicrobial activity for compound 6 at 1 mg/mL for S. aureus P-209 and E. coli M 17 strains [ 11 ]. Several recent studies have identified 3,4-dihydroquinoxalin-2(1 H )-ones 7–10 as hits for distinct biological targets [ 12 20 ], particularly antidiabetic 7 [ 20 ], anticancer 8 [ 18 ], anti-inflammatory 9 [ 16 ], and antibacterial 10 [ 19 ] ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%